1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of a Rat Hepatoma‐Derived Aldose‐Reductase‐Like Protein

Abstract: A protein detected in N-methyl-N-nitrosourea-initiated rat hepatomas by two-dimensional electrophoresis at 35 kDdpI 7.4 was identified in a previous study by internal amino acid micro sequencing as an aldose-reductase-like protein [Zeindl-Eberhart, E., Jungblut, P. R., Otto, A. & Rabes, H. M. (1994) Identification of tumor-associated protein variants during rat hepatocarcinogenesis, J. Biol. Chem. 269, 14 589-14 5941. Two-dimensional electrophoresis of rat lens proteins revealed a spot at 37 kDa/pI 6.8 that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 61 publications
3
35
0
1
Order By: Relevance
“…Human ARLP expression was shown on serial 4 m sections using the polyclonal antibody described above and the Vectastain -ABC Kit (rabbit immunoglobulin G; Vector Laboratories, Burlingame, CA) and diaminobenzidine (Sigma) as described. 8 After unmasking in diluted Target Retrieval Solution (Dako Diagnostica, Hamburg, Germany) for 30 minutes in an autoclave at 1 atm, endogenous peroxidase of the sections was inhibited by 3% H 2 O 2 . Human ARLP antibody was used in a dilution of 1:80 in antibody diluent (Dako).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human ARLP expression was shown on serial 4 m sections using the polyclonal antibody described above and the Vectastain -ABC Kit (rabbit immunoglobulin G; Vector Laboratories, Burlingame, CA) and diaminobenzidine (Sigma) as described. 8 After unmasking in diluted Target Retrieval Solution (Dako Diagnostica, Hamburg, Germany) for 30 minutes in an autoclave at 1 atm, endogenous peroxidase of the sections was inhibited by 3% H 2 O 2 . Human ARLP antibody was used in a dilution of 1:80 in antibody diluent (Dako).…”
Section: Methodsmentioning
confidence: 99%
“…These protein alterations might represent tumor markers that are useful in the diagnosis of human tumors and may also help the understanding of mechanisms of tumor induction and development. Proteome analysis of liver proteins and HCC were predominantly performed using either chemically induced hepatomas in animals (predominantly the rat [5][6][7][8][9][10] ) or human HCC cell lines, such as HepG2 and Huh7 cells, 11 BEL-7404 cells, 12 or HCC-M cells. 2,13,14 Numerous so-called tumor-associated or cancer-related proteins were identified; these provide valuable information for the establishment of HCC protein databases.…”
mentioning
confidence: 99%
“…Early proteomics studies identified tumor-associated protein variants during hepatocarcinogenesis in the rat [90]. Other cancer tissues were analyzed using proteome methods, such as of lung [91,92], liver [93], colon [77,94], bladder [95][96][97][98], heart [99] or prostate [100].…”
Section: Examples Of Successful Application Of Proteomicsmentioning
confidence: 99%
“…AKR inducing agents have included ethacrynic acid (9), ethoxyquin (19), 3Ј-methyl-4-dimethyl-aminoazobenzene (20), and N-methyl-N-nitrosourea (21), while spontaneous induction has been observed during the development of hereditary hepatitis leading to hepatocarcinogenesis (6). Hormonal regulation of AKR members has been observed during the estrous cycle (7), in the cell cycle of Leishmania major (22) and due to the effects of basic fibroblast growth factor on astrocytes (8).…”
Section: Resultsmentioning
confidence: 99%